Management of Dental Professional Education at Sam Ratulangi University Dental Hospital - Pritartha S. Anindita; Harol R. Lumapow; Joulanda A.M. Rawis; Jeffry S.J. Lengkong (JR Education, 2026)
Dental professional education requires a management system that can integrate academic standards, clinical service obligations, patient safety, and resource availability. This article analyzes the management effectiveness of dental professional education in a university dental and oral hospital through the interaction of four classical management functions: Planning, Organizing, Actuating, and Controlling (POAC, with six management resources: Man, Money, Material, Machine, Method, and Market (6M). A descriptive qualitative approach was used, drawing on interviews, document review, and field observation involving hospital management, program leadership, clinical supervisors, administrative personnel, and co-assistant students. The findings show that the management system performs unevenly across the POAC functions. Human-resource planning for clinical supervisors is relatively effective because minimum qualification standards and continuing-study strategies are recognized. However, planning for co-assistant intake, management structure, financing, materials, equipment, and patient supply remains weak. Organizing is strongest in student rotation and clinical-supervisor placement, but weak in financial authority and hospital management activation. Actuating is supported by clinical supervision procedures and curriculum implementation, yet is disrupted by limited dental units, delayed consumables, centralized finance, and insufficient patient cases. Controlling demonstrates strong patient-safety orientation and accountable financial documentation, but remains weak in clinical-supervisor calibration, material-equipment monitoring, and curriculum feedback. The study proposes a 6M-based POACE model by adding Evaluation as an autonomous management function. The model positions evaluation not merely as monitoring, but as an evidence-based feedback mechanism that recalibrates planning, organization, implementation, and control in order to improve clinical education quality, timely completion, and institutional accountability.